2012
DOI: 10.1016/j.jpsychires.2011.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Two HPA axis genes, CRHBP and FKBP5, interact with childhood trauma to increase the risk for suicidal behavior

Abstract: Childhood trauma is associated with hypothalamic–pituitary–adrenal (HPA) axis dysregulation. Both factors increase risk for suicidal behavior. Corticotropin releasing hormone (CRH) regulates the HPA axis and its actions are moderated by a high-affinity binding protein (CRHBP). We hypothesized that CRHBP variation and interaction with childhood trauma might influence suicidal behavior. Moreover, there might be an additive effect with FKPB5, another HPA axis gene previously associated with suicidality in this da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(117 citation statements)
references
References 50 publications
4
111
1
1
Order By: Relevance
“…In addition, previous evidence focused in the dorsal raphe nucleus identified juvenility and adolescence as periods of vulnerability for the modulation of the CRH system by stress (Lukkes et al, 2009). Interestingly, genetic studies in humans have pointed to an interaction between genetic variants in the Crhr1 gene and childhood maltreatment on the development of psychopathological alterations (Tyrka et al, 2009;Roy et al, 2012;Guillaume et al, 2013). Recently, a study in rhesus monkeys has shown that single nucleotide polymorphisms in the Crhr1 gene affect both anxiety temperament and metabolic activity in the anterior hippocampus and amygdala (Rogers et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous evidence focused in the dorsal raphe nucleus identified juvenility and adolescence as periods of vulnerability for the modulation of the CRH system by stress (Lukkes et al, 2009). Interestingly, genetic studies in humans have pointed to an interaction between genetic variants in the Crhr1 gene and childhood maltreatment on the development of psychopathological alterations (Tyrka et al, 2009;Roy et al, 2012;Guillaume et al, 2013). Recently, a study in rhesus monkeys has shown that single nucleotide polymorphisms in the Crhr1 gene affect both anxiety temperament and metabolic activity in the anterior hippocampus and amygdala (Rogers et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a growing body of evidence suggests an important role of genetic variants of FKBP51 in stress susceptibility and occurrence of FKBP51 correlates with stress sensitivity in mice KV Wagner et al major depression (Ising et al, 2008;Zimmermann et al, 2011). Other studies could show the involvement of FKBP51 in suicide events (Roy et al, 2012) and posttraumatic stress disorder (Sarapas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Исследования депрессивных расстройств у паци-ентов с попытками суицида в анамнезе показали ассоциацию гена FKBP5 с суицидальным поведением (Brent et al, 2010). Имеются данные, свиде-тельствующие об эффекте взаимодействия гена FKBP5 и детской психи-ческой травмы на развитие суицидального поведения (Roy et al, 2012). В исследовании 37 микросателлитных маркеров, расположенных на Х-хромосоме, было выявлено пять маркеров (DXS8051, DXS1047, DXS1001, DXS984 и DXS8106), показавших значительную ассоциацию с завершенным суицидом (Fiori et al, 2011).…”
Section: другие гены-кандидаты суицидального поведенияunclassified